2003
DOI: 10.1002/ajmg.a.20512
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence risk of preeclampsia in twin and singleton pregnancies

Abstract: The etiology of preeclampsia is unknown. The relatively high risk of recurrence of preeclampsia in subsequent pregnancies to the same mother suggests a genetic basis for the disease, but the mode of inheritance is uncertain. We compare the risk of preeclampsia in second pregnancies for mothers whose first preeclamptic pregnancy was either a singleton or a twin pregnancy. The crude and adjusted recurrence risks of preeclampsia in twin and singleton pregnancies were estimated in a population-based register inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 37 publications
8
37
0
4
Order By: Relevance
“…These findings are in agreement with other previously published studies [9,16] suggesting that PE in singletons is more likely to be superimposed on a chronic hypertensive state and is more likely to re-occur in future pregnancies, as described by Trogstad et al [18].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are in agreement with other previously published studies [9,16] suggesting that PE in singletons is more likely to be superimposed on a chronic hypertensive state and is more likely to re-occur in future pregnancies, as described by Trogstad et al [18].…”
Section: Discussionsupporting
confidence: 83%
“…The differentiation between PE in singletons versus twins in terms of maternal risk factors [8][9][10], pathogenesis [11][12][13][14], clinical manifestations [2,10,[15][16][17], and pregnancy outcome [2,10,15,16,18] have been investigated. Some of these studies are contradictive in their results, yet it seems that in many aspects, PE in twins significantly differs from PE in singletons.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results should be interpreted with caution, as the effects of L-arginine alone were not studied. Furthermore, the study population reported an exceptionally high recurrence rate of pre-eclampsia (30 %), compared with approximately up to 5-16 % recurrence risk observed in other countries [130][131][132][133]; therefore, results may not be generalizable or applicable to other obstetric populations. Of note, a small study of intravenous infusion of L-arginine in pregnant women showed a significant reduction in blood pressure, and this effect was more pronounced in those with pre-eclampsia [134].…”
Section: Potential Novel Therapiesmentioning
confidence: 99%
“…Most of the women were included from 3 registry-based studies that lack demographic and clinical detail. 31,32,38 Two authors of included registry-based studies were unable to provide the original data but offered to perform a new data-extraction. 22,38 They used the criteria from the initial study to create an extended and more recent database.…”
Section: Study Selectionmentioning
confidence: 99%